Power Quality Improvement in Distribution Networks Using Open UPQC - Sethi, Amanjyoti (My University, 2012)
In 20th century the expansion of power system and electronic devices has been grown at very fast rate. The most noticeable for electrical engineer is Power Quality in recent years. Power quality problem is an occurrence manifested as a nonstandard voltage, current or frequency that results in a failure or a misoperation of end user equipment. With Power quality Problem utility distribution networks, industrial load, sensitive load etc are suffered. With the restructuring of power systems and with shifting trend towards distributed and dispersed generation, the issue of power quality is going to take new dimensions. To overcome the problem related to power quality Custom power devices are introduced. A number of power quality solutions are provided by Custom power devices .At present, a wide range of very flexible controllers, which capitalize on newly available power electronics components are emerging for custom power applications. Among these, The Unified power quality conditioner (UPQC) is an effective custom power device for the enhancement of power quality due to its quick response, high reliability and nominal cost. A UPQC is used to compensate deep voltage sags, voltage unbalances and harmonics. It is efficiently capable of protecting sensitive loads against the voltage variations or disturbances. UPQC employs two converters that are connected to a common DC link with an energy storage capacitor. The main components of UPQC are shunt and series converters, DC capacitors low pass and high pass filters and series and shunt transformers.
M.E. (Power Systems and Electric Drives)
Keywords: UPQC; power quality; DTC